Health-related quality of life of rheumatic disease patients treatedin a specialized IPS in Medellin, Colombia (2017)
Purpose. To compare Health-Related Quality of Life (HRQOL) profiles and their associated factors in people with rheumatoid arthritis.(RA), spondyloarthritis (SpA), fibromyalgia (FM) and rheumatoid comorbidity treated in a specialized health center (SHC) in Medellin, Colombia. Methods. A cross-sectional analytical study was performed with 93 RA patients, 30 SpA patients, 41 primary FM patients and 48 secondary FM patients with a concurrent diagnosis of RA or SpA. A demographic, socioeconomic, and clinical survey (the IPAQ. International Physical Activity Questionnaire) and the SF-36 survey validated in Medellin were administered. The statistical analyses were executed using SPSS 21.0®.Results. Significant differences were found in all HRQOL dimensions among the patients, with physical performance perceived as the worst in the four groups. FM had the worst HRQOL profile, whereas the least affected group was SpA. Patients with RA and rheumatoid comorbidity shared similar HRQOL scores. The years of study, age and economic satisfaction variables were associated with the physical performance, vitality, social functioning, and mental health domains. Conclusion. The HRQOL profile was negative in patients with rheumatic diseases and lower in patients with FM. Additionally, variables or subgroups with greater deterioration were identified. This information will be useful for health activities and generate evidence in favor of incorporating HRQOL measurements into rheumatology services to complement clinical evaluations.